Alzheimer's disease development in adults with Down syndrome: Caregivers' perspectives. Issue 1 (22nd October 2019) - Ilacqua, Alexandra; Benedict, Jason; Shoben, Abigail; Skotko, Brian G.; Matthews, Theodora; Benson, Betsey; Allain, Dawn C.
Abstract: Research about Alzheimer's disease (AD) in individuals with Down syndrome (DS) has predominantly focused on the underlying genetics and neuropathology. Few studies have addressed how AD risk impacts caregivers of adults with DS. This study aimed to explore the perceived impact of AD development in adults with DS on caregivers by assessing caregiver knowledge, concerns, effect on personal life, and resource utilization via a 40‐question (maximum) online survey. Survey distribution by four DS organizations and two DS clinics resulted in 89 caregiver respondents. Only 28 caregivers correctly answered all three AD knowledge questions. Caregivers gave an average AD concern rating of 5.30 (moderately concerned) and an average impact of possible diagnosis rating of 6.28 (very strong impact), which had a significant negative correlation with the age of the adult with DS ( p = .009). Only 33% of caregivers reported utilization of resources to gain more information about the AD and DS association, with low levels of perceived usefulness. Our data reveal caregivers' misconceptions about AD development in DS, underutilization of available resources, and substantial concerns and perceived impacts surrounding a possible AD diagnosis. This study lays the foundation for how the medical community can better serve caregivers of aging adults with DS.